LOGISTICS REGRESSION MODELING ON INFANT MORTALITY RATES IN EAST JAVA PROVINCE - Burhanuddin Lazuwardi (Universitas Airlangga, 2020)
Infant Mortality Rate was death that occurs between the time after the baby was born until the baby not exactly one year old. Broadly speaked, from the side of the caused of infant mortality there are two kinds of endogenous infant death and exogenous infant mortality. Estimated about 8.8 million children whose age less than 5 years passed away. Based on previous data IDHs indicated that infant mortality has fallen by half, from 68 deaths per 1,000 live births for the 1987-1991 period to 32 deaths per 1,000 births for the 2008-2012 period. The purposed of this researched was to examine which factor most dominant influenced on infant mortality in East Java Province.This research used secondary data with a large sample of total population that consists of parents whose children (infants) died at the age <12 months. Variables in this study was infant mortality (IMR), Occupation, Education, Parity, Age of the mother during pregnancy. Access to antenatal care, Birth delivery helpers, and LBW. Inter-variables in this study tested its effect using logistic regression test. The conclusion of this study was infant mortality rated in East Java there 34 infant mortality per 1000 live birth. Factors affecting infant mortality rates was education and parity. Factors were not influenced in infant mortality such as Antenatal Care, Relief, LBW and Employment.Keywords: Baby Birth Mortality and Logistic Regression